Hostile interpretation training for individuals with alcohol use disorder and elevated trait anger: A controlled trial of a web-based intervention. (December 2017) - Cougle, Jesse R.; Summers, Berta J.; Allan, Nicholas P.; Dillon, Kirsten H.; Smith, Hillary L.; Okey, Sarah A.; Harvey, Ashleigh M.
Abstract: High trait anger is associated with more severe alcohol use problems, and alcohol has been found to facilitate aggressive behavior among individuals with high trait anger. Treatments focused on a sample with alcohol use disorder with elevated anger could reduce alcohol use problems, as well as violence and aggression. We sought to examine the efficacy of interpretation bias modification for hostility (IBM-H) in a sample with high trait anger and alcohol use disorder (AUD). Fifty-eight individuals with AUD and elevated trait anger were randomly assigned to eight web-based sessions (two per week) of IBM-H or a healthy video control condition (HVC). Measures of interpretation bias, anger, and alcohol use were administered at pre- and post-treatment and at one-month follow-up. IBM-H led to greater improvements in interpretation bias compared to HVC at post and follow-up. IBM-H also led to greater reductions in trait anger than HVC, though this was an indirect effect mediated by changes in interpretation bias. Further, IBM-H led to lower anger expression than HVC; this was a direct (non-mediated) effect. Lastly, both conditions reported decreases in alcohol use and consequences following treatment, though there were no significant differences between them. These findings provide initial support for the utility of IBM-H as a brief non-confrontational intervention for AUD with elevated trait anger. Limitations and future research directions are discussed. Highlights: Anger and alcohol use disorder co-occur and have been linked to aggression. We examined an internet treatment for hostile interpretation bias. Interpretation training was compared to a credible healthy videos condition. Interpretation training effectively reduced outcomes related to anger and aggression. Alcohol use and consequences decreased after treatment though it did not differ between conditions.